Towards sustainable nuclear energy: innovations and solutions for the future - Zohuri Cruickshank Vujić; Sovacool Ritch Hammad (Vertex, 2022)
Nuclear energy is a potential answer to climate change and energy security. This study examines technical breakthroughs, economic viability, environmental impacts, social acceptance, and policy factors for sustainable nuclear energy. The paper overviews nuclear energy's history, highlighting successes and challenges that have affected public opinion and regulatory frameworks. To get public approval, it stresses safety and waste management. This research's conceptual framework sets goals and variables to optimize sustainable nuclear energy technology implementation. The multi-objective optimization model considers budget, waste management, and electricity consumption to minimize greenhouse gas emissions, increase resource usage, and minimize total costs. The paper uses a numerical example to explain how the optimization model may be used to deploy nuclear power stations to meet numerous goals. The ideal solution shows how modern reactor designs and fuel recycling reduce environmental impacts and increase resource efficiency. To successfully integrate nuclear energy, scientific improvements, economic feasibility, appropriate waste management, and public engagement are crucial. It highlights nuclear power's ability to help solve global energy issues and create a low-carbon energy system. The study concluded that sustainable nuclear energy requires international cooperation, reduced rules, and continual research and innovation. Nuclear energy can help create a cleaner, more sustainable energy future by taking a holistic approach